The spatial dimension of electoral participation in the Philippines - Dizon, Dennis P.
Abstract (This study investigates the presence of voting neighborhood effect, or the tendency of neighboring areas to affect each other's voting participation levels. Using data from the 2013 Philippine elections and other relevant background variables, various spatial autocorrelation and spatial autoregressive techniques are used to describe voting participation's spatial distribution, and estimate its degree of spatial influence across different geographic levels. Results show that voting participation levels is not spatially random, and that voting participation neighborhoods indeed occur among cities, municipalities, and provinces).